The interaction of surface acoustic waves with arrays of thin metal dots - Huang, F; Huang, Frederick (1984)
﻿ One class of Surface Acoustic Wave (SAW) devices employs reflecting arrays to determine device characteristics. Dots of metal film and grooves have been used as reflectors; reflection is caused by the mechanical discontinuity. This research project is a study of an alternative reflector, the thin metal dot, which reflects by interacting with the electric field that accompanies the SAW on a piezo-electric material. Experimental work is done on Y-cut LiNbO3, a common SAW material, the aim being to characterise the reflection mechanism sufficiently to design devices, particularly on this material. Reflectivities of a large range of dot sizes is reported. Velocity change due to dots, another parameter required in device design, is also measured. In addition, holes in a metal film, physically the opposite of dots, are also studied. A theorectical model is developed to predict the behaviour of dots in devices. For a Z-propagating wave in LiNbO3, the SAW velocity for completely free and completely metallised surfaces were used to specify the properties of the material. For propagation in other directions on the surface, particularly near the X direction, a different acoustic mode, the Leaky Surface Wave (LSW), has an influence on SAW reflections, and the model also requires the LSW velocities under the same two conditions. The model uses these parameters, together with dot geometry, to determine reflectivity in any direction and velocity change due to the dots. The results agree well with experiments. A device (a RAC) is designed using this model, to bring out any unforseen difficulties in the use of dot arrays. The device performed as expected except for some unanticipated attenuation in the arrays, which can almost certainly be predictably allowed for in future designs, being broadband and not very severe.